Caring Behaviors Inventory-24: translation, cross-cultural adaptation and psychometric testing for use in a Swedish context - Anna Klarare; Mona Söderlund; Anna Wikman; Jenny McGreevy; Elisabet Mattsson; Andreas Rosenblad (BMC, 2021)
Abstract Background Patients' health and wellbeing are promoted when nurses successfully conceptualize caring in clinical practice. Measuring caring behaviors can advance knowledge about caring and has potential to improve caring practices and the outcomes of care. The Caring Behaviors Inventory-24 (CBI-24) is an empirical instrument for measuring caring, developed to determine perceptions of caring among patients and nurses. Since the instrument was not available in Swedish, the aim of this study was therefore to translate into Swedish and cross-culturally adapt CBI-24 for a Swedish healthcare context, and to psychometrically analyze the Swedish version of CBI-24. Methods The study used a traditional forward and back translation process in six stages: (1) two simultaneous translations by bilingual experts; (2) expert review committee synthesis; (3) blind back translation; (4) expert review committee deliberations; (5) pre-testing with cognitive interviews, and (6) psychometric evaluations. Results The translation process was systematically conducted and entailed discussions regarding semantic, idiomatic, experiential and conceptual equivalence. The cognitive interviews generated thoughts and reflections, which resulted in adjusting three items of the CBI-24 SWE. For psychometric analyses, 234 persons answered the questionnaire. Results indicated acceptable overall model fit in the χ2-value for the confirmatory factor analysis, while for the heuristic goodness-of-fit indices, the comparative fit index (CFI) and the standardized mean square residual (SMSR) indicated good model fits, and the root mean square error approximation (RMSEA) indicated an acceptable fit. Conclusions CBI-24 SWE has been shown to be a psychometrically acceptable instrument for use in Swedish research contexts. Further studies regarding the clinical usefulness of the instrument may be in order. In particular, CBI-24 SWE should be evaluated among nurses in rural areas.